Modelling and Hierarchical Control of CBTC - Atilgan, Cem; Kaymakci, Ozgur Turay (IEEE, 2018)
Over the last decade, the railway industry has a great evolution about signaling system and there is more orientation from the standard railway signaling system to the communication-based signaling system day to day. Communications-based train control (CBTC) is a very flexible and useful approach to check train activity and track operation. This system basically build upon radio communication to transfer in time and correct train control information. In this paper, we focus on model the all necessary CBTC elements with finite state automata and build CBTC control architecture with decentralized DES and support the existing control architecture with a three-level hierarchy. For the overall system, we show hierarchical consistency and that the closed-loop behavior is non-blocking. This paper gives an overview of the modelling a discrete event system about CBTC and gives control of CBTC.
Keywords: Discrete Event Systems; Hierarchical Control; Finite State Automata; CBTC; Supervisory Control Theory; Automation & Control Systems; Computer Science; Engineering